Short pedagogical training in supporting university teachers' professional vision: A comparison of prospective and current faculty teachers - Heinonen Neea; Katajavuori Nina; Murtonen Mari; Södervik Ilona (SPRINGER, 2022)
This study investigates the effects of a short pedagogical training on university teachers' professional vision and (mis)conceptions concerning teaching and learning, utilizing a mixed-methods approach. Participants' written interpretations of a video-based teaching-learning situation were analyzed and comparisons were made between prospective and current faculty teachers. Before the course, participants missed almost half of the pedagogically relevant incidents in a classroom. Generally, the short pedagogical training was successful in supporting all participants' professional vision development. The training successfully provided all teachers' with more in-depth reasoning skills as a result of the course. Thus, improvements in participants' reasoning skills were identified, but interestingly not in their noticing capability. In addition, prospective teachers had more misconceptions concerning teaching and learning both before and after the training. Finally, the study discusses the implications for research on how teachers' beliefs and conceptions are related to professional vision.